The Role of Environmental, Social, and Governance in Moderating the Influence of Tax Avoidance and Financial Distress on Firm Value - Fitriyana Fitriyana; Rosyid Nur Anggara Putra (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study aims to analyses the influence of tax avoidance and financial distress on firm value and the role of Environmental, Social, and Governance (ESG) as a moderator in non-financial companies listed on the Indonesia Stock Exchange in the 2020-2024 period. Method: This study is a quantitative study that uses secondary data from annual reports and ESG data from Bloomberg. The selection of companies was based on predetermined criteria using the purposive sampling method, which resulted in as many as 175 observations. This study was tested using panel data analysis and analysed by panel data regression with EViews 12 software. Findings: Based on the results of data analysis, it can be concluded that tax avoidance measured using ETR does not have a significant effect on the firm value. financial distress measured using Z-Score EMS has a significant negative effect on the firm value. ESG cannot moderate the influence of tax avoidance on firm value. ESG is able to weaken the negative influence of financial distress on firm value. Novelty: This study combines four variables (tax avoidance, financial distress, ESG, and firm value), which are still relatively rare, thus providing an opportunity to explore new relationships and find out how non-financial companies listed on the IDX can utilize ESG scores in weakening the influence of tax avoidance and financial distress on firm value.